(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article examines English and Uzbek proverbs and sayings as carriers of cultural metaphors. Proverbs are considered significant linguocultural units that reflect a nation’s historical experience, worldview, values, and mentality. The study provides a comparative analysis of metaphorical images found in English and Uzbek proverbs and explains their semantic and cultural characteristics through illustrative examples.